Carbon Monoxide Poisoning Secondary to Gas Geyser (Indian Journal of Case Reports, 2019)
Carbon monoxide (CO) is a non-irritating, colorless and odorless gas produced by the incomplete burning of carbon-containing fossil fuels. CO poisoning remains a leading cause of unintentional poisoning worldwide. During winters, accidental CO poisoning has been reported mostly due to incomplete burning of coal. Here, we report the case of a young female patient who presented with hypoxic brain injury due to CO poisoning while using gas geyser in bathroom. The diagnosis of CO poisoning was made on the basis of history, vital signs, blood gas, and MRI scan. The patient recovered well after high-flow normobaric oxygen therapy and showed significant resolution on follow up MRI. A high index of suspicion, early recognition of symptoms by emergency physicians followed by careful history taking can help in making a clinical diagnosis of CO toxicity.